Sustainable management of globally significant endemic ruminant livestock in West Africa: Guidelines for documenting plans supporting a breeding program - Marshall, Karen (International Livestock Research Institute, 2013)
This document is designed to assist partners of the project ‘Sustainable management of globally significant endemic ruminant livestock in West Africa (PROGEBE)’ in structuring a document detailing the plans behind their national-level animal breeding programs. It, however, will also be useful to others documenting breeding plans for developing country livestock production systems, outside of this specific project.